2012
DOI: 10.1016/j.jff.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of olive mill wastewater in the preparation of functional beverages: A review

Abstract: Olive mill wastewater Phenolic compounds Bioavailability Safety Beverage formulation A B S T R A C T The biological activities of phenolic compounds from olive mill wastewater (OMW) have extensively been studied, and shown a spectrum of highly interesting bioactivities. These properties demonstrate the potential of OMW extract for inclusion into food and beverages. This contribution provides an overview of key research describing the phenolic profile of OMW associated with health promoting activities including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 108 publications
2
73
0
4
Order By: Relevance
“…Most of the signals appeared to be due to MAG and DAG according to assignments by Sacchi et al [33] with very little contribution from TAG. The lipids content of olive mill wastewater is usually very low ranging from 1.6 to 9.8 g/L [34], which appeared to support the weak signals observed for the HE. Further, it was reported that fats and carbohydrates in olive mill wastewater degraded when they were stored and converted to sludges in open ponds [3], but Saiz-Jimenez et al [32] detected lipids in the studied OMWS.…”
Section: Characteristics Of Omws Feedstockmentioning
confidence: 63%
“…Most of the signals appeared to be due to MAG and DAG according to assignments by Sacchi et al [33] with very little contribution from TAG. The lipids content of olive mill wastewater is usually very low ranging from 1.6 to 9.8 g/L [34], which appeared to support the weak signals observed for the HE. Further, it was reported that fats and carbohydrates in olive mill wastewater degraded when they were stored and converted to sludges in open ponds [3], but Saiz-Jimenez et al [32] detected lipids in the studied OMWS.…”
Section: Characteristics Of Omws Feedstockmentioning
confidence: 63%
“…The optimum crystallization conditions (T hot = 70˚C, T cold = 5˚C) were selected in order to impose a large temperature gradient in the test solution taking into account the variation of solubility of FA and TCA with temperature. In this series of experiments, solutions were cooled in the same way as the model FA and TCA solutions, in an attempt to examine the potential of the selective recovery of high-added value products (namely PPs, which have important applications as food additives, pharmaceuticals [1]). The cooling crystallization process involves the separation of a solute based on the reduction of its solubility with decreasing temperature.…”
Section: Crystallization Of Mixture Of Fa and Tca In Hot Solutions Bymentioning
confidence: 99%
“…Due to the antioxidant activity of phenolic compounds contained in OMW, a number of researchers have demonstrated that their isolation and subsequent use in the food industry and in pharmaceuticals may have beneficial effects toward a number of human disease, including gastric and intestinal digestion and atherosclerosis [1,2]. On the other hand, the uncontrolled disposal of the produced wastewaters into aquatic receptors has serious environmental consequences leading to water pollution, contamination, eutrophication, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, these by-products are relatively rich in polyphenols. Polyphenols are bioactive molecules commonly used as antioxidants and antimicrobials in the food industry [3][4][5]. One important alternative is the utilization of by-products from olive tree culture and the olive oil industry as sources of nutrients for animals [6].…”
Section: Introductionmentioning
confidence: 99%